2008
DOI: 10.1007/s00247-008-0888-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimal imaging strategy for community-acquired Staphylococcus aureus musculoskeletal infections in children

Abstract: MRI is the preferred imaging modality for the investigation of pediatric CA-SA musculoskeletal infection because it offers superior sensitivity for osteomyelitis compared to bone scintigraphy and detects extraosseous complications that occur in a substantial proportion of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 9 publications
0
69
0
3
Order By: Relevance
“…The sensitivity has decreased as infections that have marked soft tissue involvement have increased. Currently, the sensitivity may be as low as 53% [29]. FDG PET appears to be considerably more sensitive (95%) and specific (87%).…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The sensitivity has decreased as infections that have marked soft tissue involvement have increased. Currently, the sensitivity may be as low as 53% [29]. FDG PET appears to be considerably more sensitive (95%) and specific (87%).…”
Section: Diagnostic Modalitiesmentioning
confidence: 99%
“…A recent series found that nearly 70% of community-acquired (CA) S. aureus infections [29] were associated with such extraosseous findings. An important contributor has been the rise of community-acquired MRSA, which now accounts for 30%-40% of osteomyelitis cases [32].…”
Section: Determination Of the Extent Of Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…МРТ позиционируется как предпочтитель-ный метод визуализации с высокой чувствитель-ностью (82-100 %) и специфичностью (75-99 %) в отличие от ограниченно применимых КТ и УЗИ [9,13,34]. В случае использования последователь-ности STIR МРТ имеет стопроцентную прогно-стическую ценность отрицательного результата, и диагноз остео миелита может быть исключен при отсутствии изменений на МР-томограммах [13].…”
unclassified